Meningkatkan Kolaboratif melalui Proyek Simulasi pada Mata Pelajaran IPAS untuk Meningkatkan Aktivitas Belajar Siswa Kelas V Madrasah Ibtidaiyah Negeri 4 Tebo - Hardiana Dwi Jayanti; Muhammad Solihin; Fitria Carli Wiseza (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
The low levels of learning activity, collaborative skills, and learning outcomes in Integrated Science and Social Studies (IPAS) remain a major challenge in implementing 21st-century learning, which emphasizes active student participation. Preliminary observations conducted in Class V-B of MIN 4 Tebo revealed that most students demonstrated limited participation in group discussions, ineffective task distribution, and learning outcomes that had not yet met the expected minimum mastery criteria. This study aimed to improve students' learning activities, collaborative activities, and learning outcomes through the implementation of the Project Based Learning (PjBL) model based on a Mount Merapi simulation in IPAS learning. The study employed a Classroom Action Research (CAR) approach using the Kemmis and McTaggart model, which consisted of two cycles involving planning, action, observation, and reflection stages. The research participants were 16 fifth-grade students of Class V-B at MIN 4 Tebo. Data were collected through observations, achievement tests, interviews, and documentation, while the data were analyzed using descriptive quantitative and qualitative techniques. The findings indicated that the implementation of Project Based Learning based on the Mount Merapi simulation significantly improved students' learning activities from 62.5% in Cycle I to 93.8% in Cycle II. Students' collaborative activities also increased from 47.8% to 86.3%, while learning mastery improved from 64.3% to 100%, with the class average score reaching 86.6 in Cycle II. These findings demonstrate that project-based learning effectively promotes active student engagement, strengthens collaborative skills, and enhances conceptual understanding through contextual and meaningful learning experiences. Therefore, the Project Based Learning model based on the Mount Merapi simulation can serve as an effective instructional alternative for improving the quality of IPAS learning in elementary schools.